2006
DOI: 10.1038/sj.ki.5000270
|View full text |Cite
|
Sign up to set email alerts
|

Progression of kidney dysfunction in the community-dwelling elderly

Abstract: Despite the high prevalence of chronic kidney disease among the elderly, few studies have described their loss of kidney function. We sought to determine the progression of kidney dysfunction among a community-based cohort of elderly subjects. The cohort included 10 184 subjects 66 years of age or older, who had one or more outpatient serum creatinine measurements during each of two time periods: 1 July to 31 December 2001 and 1 July to 31 December 2003. A mixed effects model, including covariates for age, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
223
2
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(275 citation statements)
references
References 44 publications
34
223
2
16
Order By: Relevance
“…Second, the subsample of 610 participants was not randomly drawn from the entire cohort of 2073 but was asked to have iohexol measured after enrollment in the BIS, potentially introducing selection bias. When the MDRD study equation was used (Appendix Table 6), the prevalence of eGFR less than 60 mL/min per 1.73 m in our iohexol subsample was approximately 7% less than the prevalence rates in other community-dwelling elderly cohorts (7,50). The rate of participants with albuminuria was similar to another representative sample (51).…”
Section: Discussionmentioning
confidence: 51%
“…Second, the subsample of 610 participants was not randomly drawn from the entire cohort of 2073 but was asked to have iohexol measured after enrollment in the BIS, potentially introducing selection bias. When the MDRD study equation was used (Appendix Table 6), the prevalence of eGFR less than 60 mL/min per 1.73 m in our iohexol subsample was approximately 7% less than the prevalence rates in other community-dwelling elderly cohorts (7,50). The rate of participants with albuminuria was similar to another representative sample (51).…”
Section: Discussionmentioning
confidence: 51%
“…However, eGFR decreases with aging (21,22). Therefore, adding elderly persons to the traditional CKD screening approach may be efficient in detecting individuals with mildly impaired GFR, but it may not be the most efficient approach to detect CKD cases at increased risk for CKD complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results of small study of the Baltimore Longitudinal Study on Aging also supported the findings, where an average GFR decline was 0.75 mL/min/year in men as evaluated with creatinine clearance (7). Similarly, in a longitudinal community-based study of a 2-year follow up of the elderly Canadians, Hemmelgarn et al reported that the rate of GFR decline was 0.8 mL/min/1.73 m 2 /year in women and 1.4 mL/min/1.73 m 2 /year in men in age Rate of Decline in GFR (mL/min/1.73 m group 66 years or older (about age 76 on average) without diabetes (10). However, these studies had critical disadvantages, because the study was conducted with a cross-sectional design (9) or with small number of subjects (7), and the loss of kidney function was analyzed using dichotomous outcomes (10) or evaluated based on creatinine clearance (7).…”
Section: Discussionmentioning
confidence: 99%